PERSONNEL POLICY OF HOTEL COMPANIES DURING THE CRISIS - M. Zhukova (Вестник университета)
Considered and analyzed possible scenarios of functioning hotels during the crisis shows the features of the implementation of the personnel policy of the hotel, depending on the scenario of development of hotel business. Proposed a number of measures to effectively overcome the hotel companies of the crisis in the field of human resources policy, namely the definition of the feasibility of increasing / reducing the personnel, of the availability in a hotel of low value and valuable employees, the formation of the list of methods and means of motivating highly skilled and valuable for the employees of the hotel, carrying on the formation of work management reserve of its own personnel or to attract from professionals.